A Look Back at the Gatehouses and Mansions of American Criminal Procedure - Kamisar, Yale (2015)
I am indebted to Professor William Pizzi for remembering—and praising—the “Gatehouses and Mansions” essay I wrote fifty years ago. A great many articles and books have been written about Miranda. So it is nice to be remembered for an article published a year before that famous case was ever decided